First lab results of the WEAVE fibre positioner system - Schallig, E; Lewis, I; Dalton, G; Brock, M; Terrett, D; Abrams, D; Middleton, K; Bishop, G; Aguerri, J; Bonifacio, P; Licea, E; Trager, S; et al. (Society of Photo-optical Instrumentation Engineers, 2018)
WEAVE is the new wide-field spectroscopy facility for the prime focus of the William Herschel Telescope on La Palma in the Canary Islands, Spain. It is a multi-object “pick-and-place” fibre-fed spectrograph with a 960 fibre multiplex behind a new dedicated 2° prime focus corrector. We provide an update on the fibre positioner's technical progress. The hardware has been fully assembled and integrated with its control system for testing. We have made initial calibrations and are starting to move test fibres. In the near future we will dismantle for final modifications and surface anodising, before final reassembly and full fibre installation.